Algebra Thinking Process on Vocational School Students in Completing Line Problems - Astutik Talun NU (KOLOKIUM Jurnal Pendidikan Luar Sekolah, 2019)
This research is motivated by the observations of researchers when teaching, it was found that there are still many students who experience obstacles when solving row problems. This type of research is qualitative research with descriptive research type. The approach and type of study were chosen according to the researcher's goal which is to describe the students' algebraic thought processes in solving the problem of ranks. The findings in this study, namely high ability students can go through each stage of problem-solving as well as doing the algebraic thinking process well, while moderate and low ability students still often ignore the stage of looking back. They also still have difficulty doing the algebraic thought process. The algebraic thinking process of high-ability students is more complex than students of medium and low ability. Highly capable students experience the process of gathering ideas, clarifying ideas, evaluating ideas, and making decisions over and over again in the thought process he does in solving problems. Besides that, in the process of thinking, high-ability students also observe patterns, make generalizations, use meaningful symbols, use functions, and make mathematical models.